Effect of different acidulants on shelf life of chhana podo at ambient temperature - S. S. Bankar; M. Raziuddin; P.N. Zanjad; Adil Shaikh (Indian Journal of Veterinary and Animal Sciences Research, 2023)
Present study was undertaken to evaluate the shelf life of chhana podo prepared from 1% citric acid and 2% lactic acid and stored at ambient temperature (30+ 20 C). Microbial, physico-chemical and sensory qualities of product were studied during storage. The chhana podo were analyzed Standard Plate Count (SPC), yeast and mould count on alternate days. The SPC, yeast and mould count increased significantly (P